2016
DOI: 10.3390/en9110965
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Biogas Production on Farmland Rental Prices: Empirical Evidences from Northern Italy

Abstract: Abstract:In the last decade, increased environmental awareness has prompted the adoption of incentives for exploiting renewable energy sources. Among these, biogas production has received a certain attention in developed countries. Nonetheless, the subsidies provided have posed the problem of an activity (the production of bioenergy) that engages in direct competition with food and feed production for limited resources, like agricultural land. Even if this competition may be softened by allocating marginal lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…The second one is related to different uses of maize in each area within the region. In those areas where livestock production is the core farming activity, maize represents the main (and less expensive) source of in-farm feed; for this reason, and for the recent expansion of biogas plants (Bartoli et al, 2016, Demartini et al, 2016, the demand for maize has locally increased, and it is therefore difficult to replace such crop with others. While in other areas of the region, where animal productions are not prevalent, maize monoculture is less frequent and it may enter more frequently in rotation with other crops, making its producers more compliant to crops diversification commitment from the start.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second one is related to different uses of maize in each area within the region. In those areas where livestock production is the core farming activity, maize represents the main (and less expensive) source of in-farm feed; for this reason, and for the recent expansion of biogas plants (Bartoli et al, 2016, Demartini et al, 2016, the demand for maize has locally increased, and it is therefore difficult to replace such crop with others. While in other areas of the region, where animal productions are not prevalent, maize monoculture is less frequent and it may enter more frequently in rotation with other crops, making its producers more compliant to crops diversification commitment from the start.…”
Section: Discussionmentioning
confidence: 99%
“…Such zones (the plain and the hill) concentrates 85% of regional UAA, almost 100% of arable crops, 87% of permanent crops and 17% of permanent grassland. In these areas the main part of the UAA is devoted to cereals and forage crops, partly devoted to biogas production (Bartoli et al, 2016, Demartini et al, 2016. It is worth of attention that before 2015 farming practices similar to greening commitments were included among agri-environmental measures in the regional Rural Development Programme, with a fair amount of participation among eligible farmers (Bertoni et al, 2011).…”
Section: The Reference Areamentioning
confidence: 99%
“…Farms decide whether to use maize to feed animals or as an input to biogas plants. In fact, biogas plants are operational in highly-productive agricultural areas with direct competition between food, feed and energy crops in limited areas of land (Demartini et al, 2016). Farmers often increase production of maize for renewable energy production which indirectly increases its profitability.…”
Section: Resultsmentioning
confidence: 99%
“…In line with this, Appel et al [45] show that farms that also produce bioenergy offer higher prices on the land lease market and are more competitive. In their study from Northern Italy, Demartini et al [46] show a non-linear effect of biogas production on land rental prices. Hennig and Latacz-Lohmann's [44] study on the effects of biogas production on farmland rental rates in Northern Germany found that biogas production, in combination with local competition, as well as agglomeration economies resulting from high livestock densities, has a considerable impact on regional farmland rental rates.…”
Section: (€022) Andmentioning
confidence: 95%